Chinese character learning with the aid of an ICT website among Mandarin Second Additional Language learners in South Africa: a case study - Fu, Shuying (Rhodes University, Faculty of Education, Department of Education)
The teaching of Mandarin as a Second Additional Language (SAL) in South African schools was only introduced in 2016. The year 2018 saw the first Mandarin as SAL National Senior Certificate examination. Little research has been done on the teaching and learning of Mandarin as a SAL subject at the high school level in South Africa. Character learning and teaching are some of the most challenging aspects of this language teaching and learning. This research sought to investigate how beginner Mandarin SAL learners can be supported by a particular Information Communication Technology (ICT) website, www.archchinese.com (Arch Chinese), in their character learning. Learners' ability to memorise Chinese characters is of utmost importance for their success in this language learning, especially for matriculants. To support the main research goal, this study set out to investigate the requirements for Chinese character learning, the role the website Arch Chinese plays in learners' character learning and Mandarin SAL learners' experience of using Arch Chinese as a learning tool. This research was conducted in the form of a case study within the interpretative paradigm. It adopted a questionnaire and document analysis for data collection to gain insight into the research topic. To get answers to the research questions posed above, the study analysed the Curriculum Assessment Policy Statement (CAPS) Mandarin SAL documents from Grade 4"“12, the Independent Examination Board (IEB) Mandarin Subject Assessment Guidelines (SAGs), and a textbook for beginners, Learn Chinese with me: Student's book 1 in relation to character learning. The features and functions of the website, Arch Chinese, were also evaluated and Mandarin SAL learners' answers to a questionnaire on their use of the website Arch Chinese were analysed. The study found that character teaching and learning has not been given enough attention in the curriculum. It was only covered in the Intermediate Phase but was seldom mentioned in the Senior and Further Education and Training Phases in the curriculum. The CAPS Mandarin SAL documents do not consider the special characteristics of the Mandarin language, as this curriculum was based on the CAPS English Generic SAL document. As a result, the assessment requirements on writing (character count requirement in particular) were not realistic. The teaching approaches promoted in the curriculum and the teaching time do not correspond well with the teaching and learning of this language. Moreover, this study found that there was no vocabulary list prescribed in the curriculum and therefore a gap exists between the curriculum on paper and the curriculum in practice. The analysis of the IEB SAGs found that the assessments were suitable for the level of Mandarin SAL learners. This is because the IEB considered the characteristics of the Mandarin language, which is non-cognate, to the alphabet-based languages that respondents in this research spoke or were familiar with. At the same time, the analysis of the website and the learners' questionnaire found that learners held a positive attitude towards their use of the website and that it proved to help facilitate Mandarin SAL learners in their character learning. This study ends with recommendations for teachers, policy makers, the IEB, and character-learning websites.
Keywords: Mandarin dialects-- Study and teaching (Secondary) -- South Africa; Mandarin dialects Computer-assisted instruction for English speakers; Second language acquisition; Chinese characters; Information technology -- South Africa; Educational technology -- South Africa; Arch Chinese